Implementation of Subsidized Fertilizer Policy in Poleonro Village, Gilireng District, Wajo Regency - Sitti Aminah; Besse Herlina; Mudirno N (Jurnal Office, 2022)
This study aims to identify, understand and explain; 1). Implementation of subsidized fertilizer policy in Poleonro Village, Gilireng District, Wajo Regency, and 2). Supporting and inhibiting factors for implementing subsidized fertilizer policy in Poleonro Village, Gilireng District, Wajo Regency. This research is a type of qualitative research, with descriptive analysis methods in order to find facts and interpretations correctly and accurately regarding policy implementation. The data validity testing technique used in this study uses an interactive model from Miles and Huberman to analyze the research data. Activities in qualitative data analysis are carried out interactively and take place continuously until complete and saturated data is obtained. The results showed that; The implementation of the subsidized fertilizer policy in Poleonro Village, Gilireng District, Wajo Regency has generally been running according to the existing regulations, although there are still some things that need to be improved in the implementation process. Supporting factors for the implementation of subsidized fertilizer policy in Poleonro Village, Gilireng District, Wajo Regency, among others, Communication, Resources, Disposition, and Bureaucratic Structure.